Survey on Transfaulty Behaviour of Nodes in Wireless Sensor Networks - Asha, KR; Supriya, MC (International Journal of Computer Sciences and Engineering, 2025)
Unattainable environments are monitored by low-power Multi-functional sensor nodes of WSN. Wireless Sensor nodes are capable of sensing, computing and communicating the happenings in the environment. Whenever an area monitored by wireless sensor networks, is exposed to radiations or electromagnetic waves, sensor nodes will be deactivated or damaged. Then nodes are temporarily isolated. This leads to the formation of the holes of dynamic nature and also functionality of WSN components will be stopped. Thus it has consider as transfaulty behavior of nodes in WSNs. This paper reviewed the existing systems in highly structured manner related with transfer of communication mode to work in radiation-prone environments and continue to communicate between sensor nodes to identify the better route to reach destination. so as to avoid work load of each node in finding route, to avoid drain of cluster head energy, and to reduce the amount of the data which will forwarded from cluster to base station for reliable data transaction during transfaulty behavior of nodes. In order to understand the factors related, here survey of several research approaches have been analysed and presented to give a best mechanisms for avoiding communication failure due to explosion of radiations in the area monitored by wireless sensor networks.